Busy builders - Munro, Roxie (Marshall Cavendish Children, 2012)
The tiny creatures in this book are amazing builders. Can you guess which builder makes separate chambers for nurseries and even trash? Or which insect s home looks like cotton candy? Or what kind of insect has ears on its knees? Busy Builders features eight insects, one spider, and an inside look at the unique structures they each build.